2020
DOI: 10.1056/nejmoa1915103
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban for the Treatment of Venous Thromboembolism Associated with Cancer

Abstract: BACKGROUNDRecent guidelines recommend consideration of the use of oral edoxaban or riva roxaban for the treatment of venous thromboembolism in patients with cancer. However, the benefit of these oral agents is limited by the increased risk of bleed ing associated with their use. METHODSThis was a multinational, randomized, investigatorinitiated, openlabel, noninfe riority trial with blinded central outcome adjudication. We randomly assigned consecutive patients with cancer who had symptomatic or incidental acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
812
11
57

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 785 publications
(904 citation statements)
references
References 18 publications
24
812
11
57
Order By: Relevance
“…After exclusion of 716 records based on information drawn from title and abstract, 39 records were selected for full‐text assessment. Of those, we identified 4 clinical trials contributing to 9 different publications, including 5 publications on specific subgroups or post hoc analysis or on outcomes during extended treatment beyond 6 months 12‐15,22‐26 . Figure 1 shows a Preferred Reporting Items for Systematic Reviews and Meta‐Analyses flow diagram, which summarizes the process of study identification and selection 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After exclusion of 716 records based on information drawn from title and abstract, 39 records were selected for full‐text assessment. Of those, we identified 4 clinical trials contributing to 9 different publications, including 5 publications on specific subgroups or post hoc analysis or on outcomes during extended treatment beyond 6 months 12‐15,22‐26 . Figure 1 shows a Preferred Reporting Items for Systematic Reviews and Meta‐Analyses flow diagram, which summarizes the process of study identification and selection 27 …”
Section: Resultsmentioning
confidence: 99%
“…Selected studies found eligible for inclusion were the Hokusai VTE Cancer trial, SELECT‐D (Anticoagulation Therapy in Selected Cancer Patients at Risk of Recurrence of Venous Thromboembolism), ADAM VTE (Apixaban and Dalteparin in Active Malignancy Associated Venous Thromboembolism) trial, and the Caravaggio (Apixaban for the Treatment of Venous Thromboembolism in Patients With Cancer) study 12‐15 . These studies all represent RCTs, which compared DOACs with LMWHs for the treatment of VTE in patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence supporting the use of direct oral anticoagulants (DOAC) have recently become available with the publication of two dedicated noninferiority trials and one large pilot study [14][15][16] demonstrating that DOAC are non-inferior to LMWH for the prevention of recurrent VTE in this specific population, but confer a higher risk of bleeding in patients with gastrointestinal and genitourinary malignancies, which provided a significant advance in the field [17,18]. In light of these results, both DOAC and LMWH are now recommended as first-line option for the treatment of CAT by all recent guidelines [19][20][21].…”
Section: Recent Surgery Hospitalization Central Venous Cathetersmentioning
confidence: 99%
“…While in the landmark CLOT [10] and CATCH [13] studies, and more recently in the pilot (Anticoagulation Therapy in Selected Cancer Patients at Risk of Recurrence of Venous Thromboembolism) SELECT-D study [15], "active cancer" was defined according to the Haemostasis and Malignancy SSC broad definition [22], the HOKUSAI VTE Cancer trial [14] and the recently published CARAVAGGIO trial [16] allowed including patients with "Cancer diagnosed within 2 years before enrolment" (i.e., with a "history of cancer").…”
Section: Various Definitions Of Active Cancer Have Been Used In Clinimentioning
confidence: 99%
See 1 more Smart Citation